An online cost allocation model for horizontal supply chains. (January 2021) - Zou, Han; Dessouky, Maged M.; Hu, Shichun
Highlights: A cost-sharing method, HPOCS, for an online dynamic routing system is developed. HPOCS possesses desirable properties such as online fairness and budget balance. Modification to HPOCS is made to provide incentive for customers to request early. Numerical results show the benefits of the mechanisms in computing the cost shares. Abstract: Emerging technologies in cargo shipping delivery have provided a way to facilitate horizontal cooperation in the transportation of goods to reduce the shipping cost of the cooperating firms, but an open question in this cooperation is how to allocate the costs fairly among the participants. In this paper, we focus on routing in real time a fleet of capacitated vehicles to satisfy requests submitted by a set of customers with some of the requests unknown while assigning the service cost fairly among the requested customers. We propose a Hybrid Proportional Online Cost-Sharing (HPOCS) mechanism to tackle the cost-sharing problem and analyze its performance using simulation instances. Although HPOCS does satisfy the desirable properties, namely online fairness, budget balance, immediate response, individual rationality and ex-post incentive compatibility, it has a few drawbacks in certain scenarios. Therefore, we make two extensions to HPOCS: 1) we introduce the idea of discounts to encourage customers to request in advance to facilitate efficient vehicle routing; 2) we incorporate periodical re-optimization within the dynamic vehicle routing framework. Experimental analysis are made in both extensions to see the tradeoff between the performance and the loss of certain desirable properties.